2022
DOI: 10.3389/fimmu.2022.961796
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic viruses combined with immune checkpoint therapy for colorectal cancer is a promising treatment option

Abstract: Immunotherapy is one of the promising strategies in the treatment of oncology. Immune checkpoint inhibitors, as a type of immunotherapy, have no significant efficacy in the clinical treatment of patients with pMMR/MSS/MSI-L mCRC alone. Therefore, there is an urgent need to find combination therapies that can improve the response rate of immune checkpoint inhibitors. Oncolytic viruses are a new class of cancer drugs that, in addition to directly lysing tumor cells, can facilitate the action of immune checkpoint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 82 publications
0
10
0
Order By: Relevance
“…Oncolytic viruses: Oncolytic viruses are genetically modified viruses and play a role in cancer therapy by preferentially replicating in the tumor cells causing its lysis and further by stimulating the immunity of the host. Various oncolytic viruses such as vaccinia virus, Reo, herpes simplex virus, and adenovirus and oncolytic measles virus have shown promise in the treatment of Colo-rectal cancer[ 23 ].…”
Section: Newer Developments/innovations Affecting the Gi Surgerymentioning
confidence: 99%
“…Oncolytic viruses: Oncolytic viruses are genetically modified viruses and play a role in cancer therapy by preferentially replicating in the tumor cells causing its lysis and further by stimulating the immunity of the host. Various oncolytic viruses such as vaccinia virus, Reo, herpes simplex virus, and adenovirus and oncolytic measles virus have shown promise in the treatment of Colo-rectal cancer[ 23 ].…”
Section: Newer Developments/innovations Affecting the Gi Surgerymentioning
confidence: 99%
“…One study identified four phages in increased abundance in CRC patients [88]. Cancer virotherapy is immunotherapy that uses genetically modified viruses (oncolytic viruses) to selectively target and lyse cancer cells and also facilitates the activity of immune checkpoint inhibitors, which may be beneficial in the treatment of CRC [89]. The identification of phages' activity against oncogenic bacteria in the tumor microenvironment may offer a targeted therapeutic approach.…”
Section: Intestinal Virome and Crcmentioning
confidence: 99%
“…Following OV infection of tumour cells and subsequent local inflammation, innate immune cells, such as dendritic cells (DCs), natural killer (NK) cells and macrophages within the TME, recognize the DAMPs, PAMPs and tumour antigens released by oncolysis, resulting in the secretion of inflammatory cytokines, such as interferon-γ (IFN-γ), IFN-α, interleukin-6 (IL-6), IL-12 and tumour necrosis factor-α (TNF-α), which promote the maturation of DCs and further recruitment and activation of innate immune cells [ 19 , 20 ] ( Figure 2 ). Antigen-loaded antigen-presenting cells (APCs) then migrate to draining lymph nodes where they initiate antigen-specific T cell priming and activation.…”
Section: Oncolytic Virusesmentioning
confidence: 99%